Phototherapy induced hypocalcemia in neonates: A case - Goyal, Madhu; Sharma, Rambabu; Dabi, D R (Indian Journal of Child Health, 2018)
Objective: The objective of the study was to evaluate the adverse effects of phototherapy both total and ionic calcium levels in neonates. Methods: A case–control prospective study was conducted in the Department of Pediatrics, over a period of 15 months. All neonates preterm or term with icterus in phototherapy range formed the study group(s). Serum calcium total and ionized were measured on a serial basis. Results: Neonates in the study group had significant fall in total serum calcium after phototherapy (0.94±0.49 mg/dl). Similarly, ionized serum calcium also decreased after phototherapy in study group (0.56±0.36 mg/dl), p